PENGARUH PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM DENGAN RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) SEBAGAI VARIABEL MEDIASI (STUDI PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017) - Ika Octaviani N.K; Ngatno Ngatno (Universitas Diponegoro, 2019)
The capital market is a means of funding for companies and other institutions and as a means for investing activities. This study aims to determine the effect of sales growth on stock prices with Return On Assets (ROA) and Return On Equity (ROE) as study mediation variables in food and beverages sub-sector companies listed on the Indonesia Stock Exchange for the period 2015-2017. This study uses quantitative research methods. Data from this study uses secondary data in the form of company financial reports that are officially published by the Indonesia Stock Exchange (IDX) and the objects in the study are 16 food and beverages sub-sector companies that are listed on the Indonesia Stock Exchange during the study period. The type of data used in the study is panel data or a combination of time series data and cross section data. Analysis of the data used in this study is Simple Linear Regression Test, Multiple Linear Regression Test, t Test, and Sobel Test. The results of this study explain that sales growth has no effect on stock prices, ROA, and ROE. ROA and ROE have an influence on stock prices. ROA and ROE cannot mediate the relationship between sales growth and stock prices